2011
DOI: 10.1371/journal.pone.0027805
|View full text |Cite|
|
Sign up to set email alerts
|

Specific Capture and Whole-Genome Sequencing of Viruses from Clinical Samples

Abstract: Whole genome sequencing of viruses directly from clinical samples is integral for understanding the genetics of host-virus interactions. Here, we report the use of sample sparing target enrichment (by hybridisation) for viral nucleic acid separation and deep-sequencing of herpesvirus genomes directly from a range of clinical samples including saliva, blood, virus vesicles, cerebrospinal fluid, and tumour cell lines. We demonstrate the effectiveness of the method by deep-sequencing 13 highly cell-associated hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
203
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(207 citation statements)
references
References 34 publications
2
203
1
Order By: Relevance
“…The input DNA amount for each sample was 2 g. RNA bait was designed as overlapping 120-mers covering the EBV genome at five times coverage (25). DNA shearing, end repair, nontemplated addition of adenine nucleobase, adaptor ligation, hybridization, enrichment PCR, and all post-reaction cleanup steps were performed according to the SureSelect Illumina paired-end sequencing library protocol (version 1.3) and observing all of the recommended quality control steps.…”
Section: Methodsmentioning
confidence: 99%
“…The input DNA amount for each sample was 2 g. RNA bait was designed as overlapping 120-mers covering the EBV genome at five times coverage (25). DNA shearing, end repair, nontemplated addition of adenine nucleobase, adaptor ligation, hybridization, enrichment PCR, and all post-reaction cleanup steps were performed according to the SureSelect Illumina paired-end sequencing library protocol (version 1.3) and observing all of the recommended quality control steps.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we found that the 5= HIV integration junction does not always occur at the exact terminus of the HIV LTR and that both truncated U3 regions and nef additions appear to be present. Targeted probe-based enrichment has been used for sequence enrichment of HIV-1-derived lentiviral vectors (36), other viruses, such as human herpesviruses (37), and Merkel cell polyomavirus (38), as well as the detection of human genetic mutations (39,40). While Ustek et al were able to enrich deep sequencing libraries for the targeted lentiviral vector, over 90% of fragments that were pulled down were not complementary to the target region (36).…”
Section: Discussionmentioning
confidence: 99%
“…Defining virus population structures based on genetic variation is advantageous in determining the founder viruses and coinfecting or coresident viral variants and in defining transmission chains. Additional studies using recently reported methodologies to sequence whole viral genomes directly from clinical samples (74,75) will be critically important for identifying genetic variants associated with disease.…”
Section: Discussionmentioning
confidence: 99%